Exacerbation of Darier Disease under Interferon-α-2a Therapy with Clinical Signs of Lichen Nitidus - Ioannis Karagiannidis; Martina Brunner; Christos C. Zouboulis (Karger Publishers, 2016)
Darier disease/dyskeratosis follicularis is a genodermatosis characterized by brown, oily keratotic papules and plaques in the seborrheic areas of the face and chest. Responsible for the disease are mutations in the ATP2A2 gene, encoding SERCA2, a calcium pump of the sarco-/endoplasmic reticulum. Mechanical trauma, heat, humidity, ultraviolet B radiation, oral corticosteroids and lithium are known trigger factors of the disorder. We report on a 48-year-old German woman with a flare-up of Darier disease under interferon-α-2a (IFNα-2a) therapy with clinical signs of lichen nitidus. Due to the fulminant course of the eruption, we suspected IFNα as a possible trigger. To our knowledge there are no reports regarding exacerbation of Darier disease during IFNα therapy. Possible pathogenetic mechanisms are being discussed.